Isotope Shifts of Radium Monofluoride Molecules - Udrescu, S. M.; Brinson, A. J.; Ruiz, R. F. Garcia; Gaul, K.; Berger, R.; Billowes, J.; Binnersley, C. L.; Bissell, M. L.; Breier, A. A.; Chrysalidis, K.; Cocolios, T. E.; Cooper, B. S.; et al. (Physical review letters, 2021)
Isotope shifts of 223–226,228Ra19F were measured for different vibrational levels in the electronic transition A2II1/2 ← X2Σ+. The observed isotope shifts demonstrate the particularly high sensitivity of radium monofluoride to nuclear size effects, offering a stringent test of models describing the electronic density within the radium nucleus. Ab initio quantum chemical calculations are in excellent agreement with experimental observations. These results highlight some of the unique opportunities that short-lived molecules could offer in nuclear structure and in fundamental symmetry studies.